An origami-structured triboelectric vibration energy harvester - Yoon, Hee Soo (Nanyang Technological University, 2024)
In 2012, a triboelectric nanogenerator (TENG) was first invented as a powerful energy harvesting and self-powered sensing technology, based on the coupling effect of contact electrification and electrostatic induction. With its capabilities in converting irregular, disturbed, and “wasteful” mechanical energy into electrical power, it has shown promising utility in low-cost, simple structure. Integrating this principle with the ancient Japanese art of paper folding, to create complex flexible and deformable 3D TENGs from a 2D sheet substance, it effectively increases the surface area for maximum electrostatic induction in the TENG. This project aims to harvest vibrational energy using Origami TENGs (O-TENGs) using a bellow fold structure. A prototype will be designed using different materials. Experiments will be conducted on testing the proof of concept and performance of the O-TENG under the contact separation mode in Nanyang Technological University’s Civil Engineering laboratories. This experiments consists of, but not limited to, the testing different parameters of analysis by observing the displacement of the contact separation and voltage output.